Sistem Pakar Diagnosa Kerusakan Mesin Sepeda Motor Transmission Automatic dengan Metode Forward Chaining Studi Kasus: AHASS 00955 Mitra Perdana - Imron Imron; Miftah Nur Afidah; M Sinta Nurhayati; Sulistiyah Sulistiyah; Fatmawati Fatmawati (Universitas Batanghari Jambi, 2019)
Implementation of Expert System Diagnosis of motorcycle engine damage is a solution of motorcycle service at AHASS 00955 Mitra Perdana, Expert System is a system that is related to the knowledge possessed by experts and technology users to solve a problem. This article, discusses the design of decision-making applications that have an important role in the process of diagnosing motor engine damage. Because the system is currently running the user only hands over the motorcycle to the technician. The use of computer-based artificial intelligence can be a solution to problems in structured decision making. The design of this expert system is designed using the forward tracking inference method and is designed in the form of a website to facilitate users in using it.